Principals’ Personality, Leadership, Teachers’ Job Satisfaction and Students’ Achievement - Purnomo, Halim; Karim, Abdul; Rahmatullah, Azam Syukur; Sudrajat, Sudrajat (International Journal of Psychosocial Rehabilitation, 2020)
This research is motivated by the gap between the behavior of the principal, leadership styles, teacher performance, and student success, leading to ineffective communication relationships. Basically, the behavior of school principals has a major role, a key and vital factor for the development of the education system towards an excellent school. The purpose of this work was to analyze the interconnection among principals' behavior and teachers’ job satisfaction and analysis it’s roles in figuring the student achievement. In accordance with the objectives to be achieved, the type of this research was literature study by qualitative research approach, with research instruments of an observation and documentation. The collected data would be analyzed employing data collection, the researcher made data reduction, data presentation, and conclusion. Data validation is needed by triangulation to ensure the stability and correctness of the data collected and recorded. The results showed that there was an interconnection between the school principals personality with the teachers’ job satisfaction and had a roles in affecting the student achievement. The implications of this finding, which are in the form of data about the effective behavior of principals and job satisfaction, can contribute to the development of knowledge and policies, especially in the fields of psychology and management.